ISO 14001 Environmental Standard: Process Approach and Identification of Environmental Aspects and Impacts (Global Journal of Science Frontier Research, 2024)
Environmental management is the management of activities that may have an impact on the environment 1 It aims to limit polluting emissions and risks to the environment and to save natural resources 2 Often unsuspected and therefore without us always realizing it all economic activities can have a considerable impact on the environment 3 Indeed the manufacture of products requires the extraction of raw materials and the use of water and energy 4 Similarly activities associated with the manufacturing process such as maintenance transportation all have environmental impacts 5 The environmental management system is a progress tool that integrates the environmental dimension into an organization s strategy leading it to set objectives achieve and maintain performance through effective management and promotes anticipation the forecast There is a multitude of guides allowing self-diagnosis by the organization and which make it possible to make an environmental assessment ISO 14001 is the environmental management standard created by the international organization for standardization 6 It defines the requirements of a global environmental management system for self-reporting or certification purposes 7 It is organized in 17 points modeled on quality management well known for 34 years in the industry The standard does not establish any absolute requirement for environmental performance other than a commitment to environmental policy to comply with legislation and the principle of continuous improvement 8